Acquisition of resources from foreign parents by international joint ventures : the case of Vietnam. - Nguyen, Duc Tri. (2008)
This study examines Resource Acquisition from foreign parents by international joint ventures in Vietnam. Discussed on Vietnam's economic, characteristics and the contribution of international joint ventures to the economic development of the country.